Medicalization of Sport? A Mixed-Method Study on the Use of Medications in Elite Ice Hockey - Sofie Christensen; Astrid Gjelstad; Ingunn Björnsdottir; Fredrik Lauritzen (MDPI AG, 2024)
Ice hockey is a high-risk sport known for its dominant macho culture. The purpose of this study was to examine experiences surrounding medication use among male, elite ice hockey players in Norway. A mixed-method design was employed, which first examined medications registered on doping control forms (DCFs) (n = 177) and then involved semi-structured focus group interviews (n = 5) with elite athletes (n = 25). Overall, 68% of the DCFs contained information about ≥1 medication. Among the most registered medications were NSAIDs and hypnotics (20% and 19% of all DCFs, respectively). During the interviews, numerous athletes reported using analgesics to manage injuries and pain caused by the sport, often being motivated by sacrificing themselves for the team during important matches and playoffs. Hypnotics were used due to high cumulative stress due to heavy training and competition load, late-night matches, and playing in a semi-professional league. Athlete support personnel (ASP), including physicians and trainers, were the athletes' main sources of information. The athletes often displayed a profound and non-critical trust in the advice and products provided to them by their team physician. The findings indicate that male, elite ice hockey players, through their excessive and somewhat ignorant use of medications, expose themselves to health risks and inadvertent doping.